High-density plugging cement paste and preparation method thereof
The high-density leak-blocking cement slurry prepared through specific proportions and chemical reaction methods solves the problems of large density differences and poor settlement stability under high-density conditions, and effectively seal and prevent cracks in high-temperature well formations Leakage improves cementing quality.
Patent Information
- Application Number
- CN202310867246.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-14
- Publication Date
- 2025-01-14
AI Technical Summary
The existing high-density leak-blocking cement slurry has a large density difference under high density conditions, resulting in easy separation of slurry materials and poor settlement stability, which cannot effectively solve the problem of well leakage, especially in the drilling process of blocking formation cracks and leak prevention effects. Not good.
Using specific ratios of G-level oil well cement, leak plugging agent, calcium carbonate, water loss reducing agent, dispersant, retarder, microsilicon powder and weighting agent, high-density leak plugging cement is prepared through specific chemical reactions and mixing methods. slurry ensures good rheological performance, adapts to high temperature conditions, and enhances the sealing ability of crack channels.
The good settlement stability and high-temperature stability of high-density leak-blocking cement slurry have been achieved, which significantly improves the sealing capacity of cracks, reduces the amount of water loss, meets the cementing construction needs of high-temperature wells, and improves the cementing quality.
Smart Images

Figure BDA0004339784170000101 
Figure BDA0004339784170000111 
Figure BDA0004339784170000112
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cement slurry preparation, in particular to high-density plugging cement slurry and a preparation method thereof. Background Art
[0002] With the continuous deepening of oil and gas exploration and development, the formations encountered during the drilling process have become increasingly complex, especially when drilling into pressure-depleted formations, fracture-developed formations, and formations with multiple pressure layers, the problem of well leakage is serious.
[0003] Well leakage seriously endangers the quality of cementing: 1) Cement slurry has low return and cannot seal the formation as designed; 2) It causes the annulus flow velocity to decrease, affecting the displacement efficiency and cementing quality; 3) It affects the quality of the cement ring and causes cross-flow between the production layer and the water layer; 4) Cement slurry leaks into the production layer, polluting the oil and gas layer and affecting oil and gas production capacity; 5) The oil and gas well is out of control.
[0004] Improper or untimely treatment of lost circulation can cause stuck drill, blowout, well collapse, and even cause the scrapping of part of the wellbore or the entire well. The frequent occurrence of lost circulation has become an important reason for the high drilling cost and long construction period. Lost circulation is particularly prone to occur in areas with developed formation fractures. In some of these areas, high-pressure oil and gas layers are buried underground, so high-density drilling fluid (2.0g / cm 3 Up to 2.4g / cm 3 ) Drilling, under the condition of narrow safety density window, if the engineering and technical measures are not reasonable, such as pulling up and down too hard, it will generate additional pressure on the well wall. Once the fracture pressure of the formation is exceeded, the formation will be fractured, causing the cracks in the well wall to expand and cause leakage. During the cementing construction process, since the density of cement slurry exceeds the density of drilling fluid, the leakage problem caused by cementing cement slurry will be more serious. Since the leakage caused by fracture formation will limit the circulation of drilling fluid and cementing displacement, and the displacement efficiency is low, the cleaning effect of flushing fluid on mud cake is reduced, and finally the cementing quality is seriously affected.
[0005] At present, the commonly used plugging treatment measures include reducing the displacement, reducing the density, and cementing plugging. Commonly used bridging, high water loss, liquid absorption and swelling, flexible gel, and curable plugging materials, together with drilling plugging and bridging plugging technologies, can block fluid flow channels such as cracks and pores. However, these plugging materials and methods cannot solve the problem of well leakage under high-density conditions. The density of high-density plugging cement slurry varies greatly, which is easy to cause segregation of slurry materials, and good settlement stability should be ensured. Summary of the invention
[0006] The present invention provides a high-density plugging cement slurry and a preparation method thereof, which overcomes the above-mentioned deficiencies of the prior art and can effectively solve the problem that the existing high-density plugging cement slurry has large density differences, which easily causes slurry material segregation and poor sedimentation stability.
[0007] One of the technical solutions of the present invention is achieved through the following measures: a high-density plugging cement slurry, wherein the raw materials include, by weight, 100 parts of G-grade oil well cement, 46 to 74 parts of water, 2.0 to 3.5 parts of plugging agent, 2.0 to 4.0 parts of calcium carbonate, 4.0 to 6.0 parts of fluid loss reducer, 1.0 to 4.5 parts of dispersant, 1.5 to 2.5 parts of retarder, 4.0 to 10.0 parts of microsilica powder, 30.0 to 45.0 parts of quartz sand and 10.0 to 150.0 parts of weighting agent.
[0008] The following is a further optimization and / or improvement of one of the above-mentioned technical solutions:
[0009] The above-mentioned plugging agent is obtained by the following method:
[0010] In the first step, 50 to 60 parts of deionized water are added into a reactor, nitrogen is introduced, and 15 to 20 parts of acrylic acid are added into the reactor under stirring;
[0011] In the second step, NaOH is added to the reactor to adjust the pH value of the solution in the reactor to 7 to 9;
[0012] The third step is to add 2.5 to 3.0 parts of acrylamide, 15 to 18 parts of 2-acrylamido-2-methylpropanesulfonic acid and 2 to 3 parts of glass fiber to the reactor in sequence, stir evenly, then drop 0.2 to 0.5 parts of ammonium persulfate, 0.2 to 0.5 parts of sodium sulfite and 0.1 to 0.3 parts of N,N-methylenebisacrylamide in sequence, control the reaction temperature of the reactor to 50°C to 60°C, rinse the reaction product 2 to 3 times until the reaction is completed, and dry it to obtain a plugging agent.
[0013] The above-mentioned fluid loss additive is obtained by the following method:
[0014] The first step is to add 30 to 40 parts of deionized water into a reactor, introduce nitrogen, and under stirring conditions, sequentially add 8 to 10 parts of 2-acrylamido-2-methylpropanesulfonic acid, 0.1 to 0.2 parts of N-vinyl imidazole, 0.1 to 0.2 parts of N-vinyl pyrrolidone, 1 to 2 parts of acrylamide and 0.2 to 0.3 parts of maleic anhydride into the reactor, and stir evenly;
[0015] In the second step, NaOH is added to the reactor to adjust the pH value of the solution in the reactor to 7 to 9;
[0016] The third step is to drop 0.1 to 0.2 parts of ammonium persulfate into the reactor, and control the reaction temperature of the reactor to 50° C. to 60° C. until the reaction is completed to obtain a fluid loss reducer.
[0017] The above retarder is retarder RCR-211S.
[0018] The above dispersant is dispersant RCY-100.
[0019] The density of the above quartz sand is 2.65g / cm 3 Up to 2.80g / cm 3 , average particle size 50μm to 120μm.
[0020] The density of the above microsilica powder is 2.00g / cm 3 Up to 2.35g / cm 3 , average particle size 1μm to 25μm.
[0021] The above-mentioned weighting agent is micro manganese (density 4.90g / cm 3 , average particle size 5μm) and iron ore powder (density 7.20g / cm 3 , average particle size 10μm to 150μm).
[0022] The high-density plugging cement slurry is obtained by the following method: first, the required amount of plugging agent, calcium carbonate, fluid loss reducer, dispersant, retarder, microsilica powder, quartz sand and weighting agent are mixed to obtain a mixture; then, the mixture and the required amount of water are added to the required amount of G-grade oil well cement and stirred evenly to obtain a high-density plugging cement slurry.
[0023] The second technical solution of the present invention is achieved through the following measures: a method for preparing a high-density plugging cement slurry is carried out as follows: first, the required amounts of plugging agent, calcium carbonate, fluid loss reducer, dispersant, retarder, microsilica powder, quartz sand and weighting agent are mixed to obtain a mixed material; then, the mixed material and the required amount of water are added to the required amount of G-grade oil well cement and stirred evenly to obtain a high-density plugging cement slurry.
[0024] The high-density plugging cement slurry of the present invention has good rheological properties, has the advantages of good adaptability to fracture channels, good water loss reduction, leakage prevention and pressure bearing effects, is suitable for cementing construction of high-temperature wells with a circulation temperature of 120°C to 150°C, and effectively addresses the problem of serious leakage risk of high-density cementing slurry in fractured formations. DETAILED DESCRIPTION
[0025] The present invention is not limited by the following embodiments, and specific implementation methods can be determined according to the technical scheme of the present invention and actual conditions. Unless otherwise specified, the various chemical reagents and chemicals mentioned in the present invention are all known and commonly used chemical reagents and chemicals in the prior art.
[0026] The present invention will be further described below in conjunction with embodiments:
[0027] Example 1: The high-density plugging cement slurry, the raw materials by weight include 100 parts of G-grade oil well cement, 46 parts to 74 parts of water, 2.0 parts to 3.5 parts of plugging agent, 2.0 parts to 4.0 parts of calcium carbonate, 4.0 parts to 6.0 parts of fluid loss reducer, 1.0 parts to 4.5 parts of dispersant, 1.5 parts to 2.5 parts of retarder, 4.0 parts to 10.0 parts of microsilica powder, 30.0 parts to 45.0 parts of quartz sand and 10.0 parts to 150.0 parts of weighting agent.
[0028] Example 2: As an optimization of the above example, the plugging agent is obtained by the following method:
[0029] In the first step, 50 to 60 parts of deionized water are added into a reactor, nitrogen is introduced, and 15 to 20 parts of acrylic acid are added into the reactor under stirring;
[0030] In the second step, NaOH is added to the reactor to adjust the pH value of the solution in the reactor to 7 to 9;
[0031] The third step is to add 2.5 to 3.0 parts of acrylamide, 15 to 18 parts of 2-acrylamido-2-methylpropanesulfonic acid and 2 to 3 parts of glass fiber to the reactor in sequence, stir evenly, then drop 0.2 to 0.5 parts of ammonium persulfate, 0.2 to 0.5 parts of sodium sulfite and 0.1 to 0.3 parts of N,N-methylenebisacrylamide in sequence, control the reaction temperature of the reactor to 50°C to 60°C, rinse the reaction product 2 to 3 times until the reaction is completed, and dry it to obtain a plugging agent.
[0032] Embodiment 3: As an optimization of the above embodiment, the fluid loss additive is obtained by the following method:
[0033] The first step is to add 30 to 40 parts of deionized water into a reactor, introduce nitrogen, and under stirring conditions, sequentially add 8 to 10 parts of 2-acrylamido-2-methylpropanesulfonic acid, 0.1 to 0.2 parts of N-vinyl imidazole, 0.1 to 0.2 parts of N-vinyl pyrrolidone, 1 to 2 parts of acrylamide and 0.2 to 0.3 parts of maleic anhydride into the reactor, and stir evenly;
[0034] In the second step, NaOH is added to the reactor to adjust the pH value of the solution in the reactor to 7 to 9;
[0035] The third step is to drop 0.1 to 0.2 parts of ammonium persulfate into the reactor, and control the reaction temperature of the reactor to 50° C. to 60° C. until the reaction is completed to obtain a fluid loss reducer.
[0036] In the present invention, the raw materials N-vinyl imidazole and N-vinyl pyrrolidone used in the preparation process of the raw material fluid loss reducer can further improve the high temperature stability of the fluid loss reducer because the two materials have a rigid ring structure.
[0037] Example 4: As an optimization of the above example, the retarder is retarder RCR-211S.
[0038] Example 5: As an optimization of the above example, the dispersant is dispersant RCY-100.
[0039] Example 6: As an optimization of the above example, the density of quartz sand is 2.65 g / cm 3 Up to 2.80g / cm 3 , average particle size 50μm to 120μm.
[0040] In the present invention, when the bottom-well static temperature reaches 110°C, high-temperature resistant cement slurry is required. The raw material quartz sand of the present invention can effectively improve the thermal stability of cement stone and is an effective admixture to prevent the strength of cement stone from declining at high temperatures. When the amount of quartz sand added reaches 30% to 40% of the mass fraction of the cement slurry, it can well prevent the decline of the strength and toughness of the cement stone and improve the plugging performance of the cement slurry.
[0041] Example 7: As an optimization of the above example, the density of microsilica powder is 2.00 g / cm 3 Up to 2.35g / cm 3 , average particle size 1μm to 25μm.
[0042] In the present invention, since the stability of ultra-high density cement slurry is a serious problem, the raw material microsilica powder has a certain suspension function, and the SiO 2 The content is helpful to the high temperature stability of cement paste. In the close packing theory, small particle components can play the role of filling and rolling, and the suspension effect is enhanced. Most of the particle sizes of the preferred small particle component microsilica powder are concentrated in 1μm to 25μm, so that the microsilica powder has a greater suspension effect and reduces water loss. At the same time, it compacts and fills cracks, giving full play to the plugging ability of the cement slurry system.
[0043] Example 8: As an optimization of the above example, the weighting agent is micro manganese (density 4.90 g / cm 3 , average particle size 5μm) and iron ore powder (density 7.20g / cm 3 , average particle size 10μm to 150μm).
[0044] Example 9: As an optimization of the above example, a high-density plugging cement slurry is obtained according to the following method: first, the required amounts of plugging agent, calcium carbonate, fluid loss reducer, dispersant, retarder, microsilica powder, quartz sand and weighting agent are mixed to obtain a mixture; then, the mixture and the required amount of water are added to the required amount of G-grade oil well cement and stirred evenly to obtain a high-density plugging cement slurry.
[0045] Embodiment 10:
[0046] The high-density plugging cement slurry includes, by weight, 100 parts of G-grade oil well cement, 46 parts of water, 2.0 parts of plugging agent, 2.0 parts of calcium carbonate, 4.0 parts of fluid loss agent, 1.0 parts of dispersant RCY-100, 1.5 parts of retarder RCR-211S, 4.0 parts of microsilica powder, 30.0 parts of quartz sand and 10.0 parts of micromanganese. The high-density plugging cement slurry is obtained by the following method: first, the required amount of plugging agent, calcium carbonate, fluid loss agent, dispersant RCY-100, retarder RCR-211S, microsilica powder, quartz sand and micromanganese are mixed to obtain a mixed material; then, the mixed material and the required amount of water are added to the required amount of G-grade oil well cement and stirred evenly to obtain the high-density plugging cement slurry. Among them,
[0047] The plugging agent is obtained by the following method:
[0048] In the first step, 50 parts of deionized water are added into a reactor, nitrogen is introduced, and 15 parts of acrylic acid are added into the reactor under stirring;
[0049] In the second step, NaOH was added to the reactor to adjust the pH value of the solution in the reactor to 7;
[0050] The third step is to add 2.5 parts of acrylamide, 15 parts of 2-acrylamido-2-methylpropanesulfonic acid and 2 parts of glass fiber to the reactor in sequence, stir evenly, then drop 0.2 parts of ammonium persulfate, 0.2 parts of sodium sulfite and 0.1 parts of N,N-methylenebisacrylamide in sequence, control the reaction temperature of the reactor to 50°C, rinse the reaction product twice until the reaction is completed, and dry it to obtain a plugging agent;
[0051] The fluid loss additive is obtained by the following method:
[0052] In the first step, 30 parts of deionized water are added to the reactor, nitrogen is introduced, and under stirring conditions, 8 parts of 2-acrylamido-2-methylpropanesulfonic acid, 0.1 parts of N-vinyl imidazole, 0.1 parts of N-vinyl pyrrolidone, 1 part of acrylamide and 0.2 parts of maleic anhydride are added to the reactor in sequence, and stirred evenly;
[0053] In the second step, NaOH was added to the reactor to adjust the pH value of the solution in the reactor to 7;
[0054] The third step is to drop 0.1 parts of ammonium persulfate into the reactor, and control the reaction temperature of the reactor to 50° C. until the reaction is completed to obtain a fluid loss reducer.
[0055] Embodiment 11:
[0056] The high-density plugging cement slurry includes, by weight, 100 parts of G-grade oil well cement, 74 parts of water, 3.5 parts of plugging agent, 4.0 parts of calcium carbonate, 6.0 parts of fluid loss agent, 4.5 parts of dispersant RCY-100, 2.5 parts of retarder RCR-211S, 10.0 parts of microsilica powder, 45.0 parts of quartz sand and 150.0 parts of iron ore powder. The high-density plugging cement slurry is obtained by the following method: first, the required amount of plugging agent, calcium carbonate, fluid loss agent, dispersant RCY-100, retarder RCR-211S, microsilica powder, quartz sand and iron ore powder are mixed to obtain a mixture; then, the mixture and the required amount of water are added to the required amount of G-grade oil well cement and stirred evenly to obtain the high-density plugging cement slurry. Among them,
[0057] The plugging agent is obtained by the following method:
[0058] In the first step, 60 parts of deionized water are added into a reactor, nitrogen is introduced, and 20 parts of acrylic acid are added into the reactor under stirring;
[0059] In the second step, NaOH was added to the reactor to adjust the pH value of the solution in the reactor to 9;
[0060] The third step is to sequentially add 3.0 parts of acrylamide, 18 parts of 2-acrylamido-2-methylpropanesulfonic acid and 3 parts of glass fiber into the reactor, stir evenly, then sequentially add 0.5 parts of ammonium persulfate, 0.5 parts of sodium sulfite and 0.1 to 0.3 parts of N,N-methylenebisacrylamide, control the reaction temperature of the reactor to 60°C, rinse the reaction product 3 times until the reaction is completed, and dry it to obtain a plugging agent;
[0061] The fluid loss additive is obtained by the following method:
[0062] In the first step, 40 parts of deionized water are added to the reactor, nitrogen is introduced, and under stirring conditions, 10 parts of 2-acrylamido-2-methylpropanesulfonic acid, 0.2 parts of N-vinyl imidazole, 0.2 parts of N-vinyl pyrrolidone, 2 parts of acrylamide and 0.3 parts of maleic anhydride are added to the reactor in sequence, and stirred evenly;
[0063] In the second step, NaOH was added to the reactor to adjust the pH value of the solution in the reactor to 9;
[0064] The third step is to drop 0.2 parts of ammonium persulfate into the reactor, and control the reaction temperature of the reactor to 60° C. until the reaction is completed to obtain a fluid loss reducer.
[0065] Embodiment 12:
[0066] The high-density plugging cement slurry includes, by weight, 100 parts of G-grade oil well cement, 60 parts of water, 3 parts of plugging agent, 3 parts of calcium carbonate, 5 parts of fluid loss agent, 3 parts of dispersant RCY-100, 2 parts of retarder RCR-211S, 8 parts of microsilica powder, 40 parts of quartz sand and 80 parts of micromanganese. The high-density plugging cement slurry is obtained by the following method: first, the required amount of plugging agent, calcium carbonate, fluid loss agent, dispersant RCY-100, retarder RCR-211S, microsilica powder, quartz sand and micromanganese are mixed to obtain a mixed material; then, the mixed material and the required amount of water are added to the required amount of G-grade oil well cement and stirred evenly to obtain the high-density plugging cement slurry. Among them,
[0067] The plugging agent is obtained by the following method:
[0068] In the first step, 55 parts of deionized water are added into a reactor, nitrogen is introduced, and 18 parts of acrylic acid are added into the reactor under stirring;
[0069] In the second step, NaOH was added to the reactor to adjust the pH value of the solution in the reactor to 8;
[0070] The third step is to add 2.8 parts of acrylamide, 16 parts of 2-acrylamido-2-methylpropanesulfonic acid and 2.5 parts of glass fiber to the reactor in sequence, stir evenly, then drop 0.4 parts of ammonium persulfate, 0.4 parts of sodium sulfite and 0.2 parts of N,N-methylenebisacrylamide in sequence, control the reaction temperature of the reactor to 55°C, rinse the reaction product 3 times until the reaction is completed, and dry it to obtain a plugging agent;
[0071] The fluid loss additive is obtained by the following method:
[0072] In the first step, 35 parts of deionized water are added to the reactor, nitrogen is introduced, and under stirring conditions, 9 parts of 2-acrylamido-2-methylpropanesulfonic acid, 0.15 parts of N-vinyl imidazole, 0.15 parts of N-vinyl pyrrolidone, 1.5 parts of acrylamide and 0.25 parts of maleic anhydride are added to the reactor in sequence, and stirred evenly;
[0073] In the second step, NaOH was added to the reactor to adjust the pH value of the solution in the reactor to 8;
[0074] The third step is to drop 0.15 parts of ammonium persulfate into the reactor, and control the reaction temperature of the reactor to 55° C. until the reaction is completed to obtain a fluid loss reducer.
[0075] Embodiment 13:
[0076] The high-density plugging cement slurry includes, by weight, 100 parts of G-grade oil well cement, 46 parts of water, 2.0 parts of plugging agent, 3.0 parts of calcium carbonate, 6.0 parts of fluid loss agent, 1.3 parts of dispersant RCY-100, 2.0 parts of retarder RCR-211S, 4.0 parts of microsilica powder, 30 parts of quartz sand and 15 parts of iron ore powder. The high-density plugging cement slurry is obtained by the following method: first, the required amount of plugging agent, calcium carbonate, fluid loss agent, dispersant RCY-100, retarder RCR-211S, microsilica powder, quartz sand and iron ore powder are mixed to obtain a mixture; then, the mixture and the required amount of water are added to the required amount of G-grade oil well cement and stirred evenly to obtain the high-density plugging cement slurry. Among them,
[0077] The plugging agent is obtained by the following method:
[0078] In the first step, 60 parts of deionized water are added into a reactor, nitrogen is introduced, and 18 parts of acrylic acid are added into the reactor under stirring;
[0079] In the second step, NaOH was added to the reactor to adjust the pH value of the solution in the reactor to 8;
[0080] The third step is to add 2.5 parts of acrylamide, 15 parts of 2-acrylamido-2-methylpropanesulfonic acid and 2 parts of glass fiber to the reactor in sequence, stir evenly, then drop 0.5 parts of ammonium persulfate, 0.5 parts of sodium sulfite and 0.2 parts of N,N-methylenebisacrylamide in sequence, control the reaction temperature of the reactor to 60°C, rinse the reaction product 3 times until the reaction is completed, and dry it to obtain a plugging agent;
[0081] The fluid loss additive is obtained by the following method:
[0082] In the first step, 40 parts of deionized water are added to the reactor, nitrogen is introduced, and under stirring conditions, 10 parts of 2-acrylamido-2-methylpropanesulfonic acid, 0.1 parts of N-vinyl imidazole, 0.1 parts of N-vinyl pyrrolidone, 1 part of acrylamide and 0.2 parts of maleic anhydride are added to the reactor in sequence, and stirred evenly;
[0083] In the second step, NaOH was added to the reactor to adjust the pH value of the solution in the reactor to 8;
[0084] The third step is to drop 0.2 parts of ammonium persulfate into the reactor, and control the reaction temperature of the reactor to 50° C. until the reaction is completed to obtain a fluid loss reducer.
[0085] Example 14: The difference from Example 13 is that the raw materials, by weight, include 100 parts of G-grade oil well cement, 46 parts of water, 3.0 parts of plugging agent, 2.0 parts of calcium carbonate, 4.0 parts of fluid loss reducer, 1.3 parts of dispersant RCY-100, 2.0 parts of retarder RCR-211S, 4.0 parts of microsilica powder, 30 parts of quartz sand and 15 parts of iron ore powder, and the remaining steps are the same.
[0086] Example 15: The difference from Example 13 is that the raw materials, by weight, include 100 parts of G-grade oil well cement, 47 parts of water, 2.0 parts of plugging agent, 4.0 parts of calcium carbonate, 4.0 parts of fluid loss reducer, 2.0 parts of dispersant RCY-100, 1.5 parts of retarder RCR-211S, 5.0 parts of microsilica powder, 30 parts of quartz sand and 45 parts of weighting agent (4.0 parts of micro manganese and 41 parts of iron ore powder), and the remaining steps are the same.
[0087] Example 16: The difference from Example 13 is that the raw materials, by weight, include 100 parts of G-grade oil well cement, 47 parts of water, 3.0 parts of plugging agent, 2.0 parts of calcium carbonate, 5.0 parts of fluid loss reducer, 2.0 parts of dispersant RCY-100, 1.5 parts of retarder RCR-211S, 5.0 parts of microsilica powder, 30 parts of quartz sand and 45 parts of weighting agent (4 parts of micro manganese and 41 parts of iron ore powder), and the remaining steps are the same.
[0088] Example 17: The difference from Example 13 is that the raw materials, by weight, include 100 parts of G-grade oil well cement, 48 parts of water, 2.0 parts of plugging agent, 4.0 parts of calcium carbonate, 4.0 parts of fluid loss reducer, 2.0 parts of dispersant RCY-100, 2.2 parts of retarder RCR-211S, 5.0 parts of microsilica powder, 30 parts of quartz sand and 63 parts of weighting agent (5.5 parts of micro manganese and 57.5 parts of iron ore powder), and the remaining steps are the same.
[0089] Example 18: The difference from Example 13 is that the raw materials, by weight, include 100 parts of G-grade oil well cement, 48 parts of water, 2.5 parts of plugging agent, 3.5 parts of calcium carbonate, 5.0 parts of fluid loss reducer, 2.0 parts of dispersant RCY-100, 2.2 parts of retarder RCR-211S, 5.0 parts of microsilica powder, 30 parts of quartz sand and 63 parts of weighting agent (5.5 parts of micro manganese and 57.5 parts of iron ore powder), and the remaining steps are the same.
[0090] Example 19: The difference from Example 13 is that the raw materials, by weight, include 100 parts of G-grade oil well cement, 52 parts of water, 2.0 parts of plugging agent, 3.0 parts of calcium carbonate, 5.0 parts of fluid loss reducer, 3.0 parts of dispersant RCY-100, 2.5 parts of retarder RCR-211S, 6.0 parts of microsilica powder, 30 parts of quartz sand and 70 parts of weighting agent (6 parts of micro manganese and 64 parts of iron ore powder), and the remaining steps are the same.
[0091] Example 20: The difference from Example 13 is that the raw materials, by weight, include 100 parts of G-grade oil well cement, 52 parts of water, 3.5 parts of plugging agent, 1.5 parts of calcium carbonate, 4.0 parts of fluid loss reducer, 3.0 parts of dispersant RCY-100, 2.5 parts of retarder RCR-211S, 6.0 parts of microsilica powder, 30 parts of quartz sand and 70 parts of weighting agent (6.0 parts of micro manganese and 64 parts of iron ore powder), and the remaining steps are the same.
[0092] Example 21: The difference from Example 13 is that the raw materials, by weight, include 100 parts of G-grade oil well cement, 68 parts of water, 3.0 parts of plugging agent, 2.0 parts of calcium carbonate, 5.0 parts of fluid loss reducer, 4.0 parts of dispersant RCY-100, 2.25 parts of retarder RCR-211S, 8.0 parts of microsilica powder, 35 parts of quartz sand and 115 parts of weighting agent (10 parts of micro manganese and 105 parts of iron ore powder), and the remaining steps are the same.
[0093] Example 22: The difference from Example 13 is that the raw materials, by weight, include 100 parts of G-grade oil well cement, 68 parts of water, 2.0 parts of plugging agent, 4.0 parts of calcium carbonate, 5.5 parts of fluid loss reducer, 4.0 parts of dispersant RCY-100, 2.25 parts of retarder RCR-211S, 8.0 parts of microsilica powder, 35 parts of quartz sand and 115 parts of weighting agent (10 parts of micro manganese and 105 parts of iron ore powder), and the remaining steps are the same.
[0094] Example 23: The difference from Example 13 is that the raw materials, by weight, include 100 parts of G-grade oil well cement, 74 parts of water, 3.5 parts of plugging agent, 2.0 parts of calcium carbonate, 6.0 parts of fluid loss reducer, 4.5 parts of dispersant RCY-100, 2.2 parts of retarder RCR-211S, 10.0 parts of microsilica powder, 45 parts of quartz sand and 135 parts of iron ore powder, and the remaining steps are the same.
[0095] Example 24: The difference from Example 13 is that the raw materials, by weight, include 100 parts of G-grade oil well cement, 74 parts of water, 2.0 parts of plugging agent, 1.5 parts of calcium carbonate, 6.0 parts of fluid loss reducer, 4.5 parts of dispersant RCY-100, 2.2 parts of retarder RCR-211S, 10.0 parts of microsilica powder, 45 parts of quartz sand and 135 parts of iron ore powder, and the remaining steps are the same.
[0096] Comparative Example 1: The difference from Example 13 is that walnut shell is used as the plugging agent, and the other steps are the same.
[0097] Comparative Example 2: The difference from Example 13 is that walnut shells are used as the plugging agent, and there is no fluid loss additive as the raw material, and the other steps are the same.
[0098] Comparative Example 3: The difference from Example 13 is that the raw materials do not contain plugging agent and fluid loss reducer, and the other steps are the same.
[0099] Comparative Example 4: The difference from Example 17 is that walnut shell is used as the plugging agent, and the other steps are the same.
[0100] Comparative Example 5: The difference from Example 17 is that walnut shells are used as the plugging agent, and there is no fluid loss reducer as the raw material, and the other steps are the same.
[0101] Comparative Example 6: The difference from Example 17 is that the raw materials do not contain plugging agent and fluid loss reducer, and the other steps are the same.
[0102] Comparative Example 7: The difference from Example 23 is that walnut shell is used as the plugging agent, and the other steps are the same.
[0103] Comparative Example 8: The difference from Example 23 is that walnut shells are used as the plugging agent, and there is no fluid loss reducer as the raw material, and the other steps are the same.
[0104] Comparative Example 9: The difference from Example 23 is that the raw materials do not contain plugging agent and fluid loss reducer, and the other steps are the same.
[0105] Embodiment 24:
[0106] The high-density plugging cement slurry obtained in Examples 13 to 24 of the present invention was subjected to performance tests including density (g / cm 3 ), thickening time (min, 130℃ / 70MPa), API water loss (mL), compressive strength (MPa, 24h / 150℃), free liquid (%), fluidity (cm) and sedimentation stability (g / cm 3 ). The performance evaluation was performed with reference to the methods specified in the national standards "GB / T 19139 Test Methods for Oil Well Cement" and "SY / T 5840 Indoor Test Methods for Bridging and Plugging Materials for Drilling Fluids". Meanwhile, comparative examples 1 to 9 of the present invention were used as comparisons, and the raw material proportions of examples 13 to 24 of the present invention and comparative examples 1 to 9 are shown in Table 1.
[0107] The test results are shown in Table 2, wherein the test temperature of the thickening test is 130°C, and the test pressure is 70MPa; the water loss is measured at 90°C after curing at 130°C for 0.5h; the compressive strength is measured at 130°C for 0.5h and then at 150°C for 24h; the sedimentation stability is measured at 90°C for 2h after curing at 130°C for 0.5h. It can be seen from Table 2 that with the increase of the content of the raw material plugging agent, the thickening time of the high-density plugging cement slurry of the present invention will be reduced, and the rheological properties of the high-density plugging cement slurry of the present invention will be less affected.
[0108] Since the plugging agent has good liquid absorption capacity, it will reduce the water loss of cement slurry suspension at high temperature, reduce the loss of water phase of the suspension, and make the various properties of cement slurry and the compressive strength of cement paste meet the relevant requirements of on-site plugging construction. Calcium carbonate can improve the plugging performance and compressive strength of cement paste and reduce the elastic modulus of cement paste.
[0109] There may be mutual influence and conflict between additives such as raw material dispersants, fluid loss agents and retarders. For example, dispersants can effectively reduce flow friction and optimize the rheology of cement slurry by improving the hydration particle grading, but at the same time, they may also make the stability of cement slurry worse and cause slurry sedimentation. Retarder can effectively prolong the thickening time of cement slurry to ensure the time for safe pumping, but it may also cause super-retarded setting or non-setting due to improper addition, resulting in a decline in cementing quality or even failure to meet the requirements of the next mining operation. Some retarders may cause flash setting, pump blocking, and "flagpole insertion" due to fluctuations in cement slurry density or in a sensitive zone for accelerating setting at a certain chemical concentration. The main function of fluid loss agents is to prevent cement slurry from losing water in high permeability layers under the action of pressure, temperature, etc., which affects construction safety and reduces the damage of cement slurry filtrate to the production layer. However, it will increase the viscosity of cement slurry, resulting in increased flow resistance and a strong retarding effect, resulting in a decrease in early strength.
[0110] The addition of the raw fluid loss agent of the present invention has little effect on the thickening time of the high-density plugging cement slurry, and has little effect on the fluidity of high-density plugging cement slurries of different densities. According to experience, the greater the water loss, the worse the sedimentation stability. The raw fluid loss agent prepared in Examples 13 to 24 of the present invention can control the API water loss of high-density plugging cement slurries of various density ranges under high temperature conditions to be within 50 mL, and the upper and lower density difference of the high-density plugging cement slurry is within 0.05 g / cm 3 Within.
[0111] Embodiment 25:
[0112] The high-density plugging cement slurries obtained in Examples 13 to 24 of the present invention were tested for plugging performance and compressive strength. At the same time, since there was no raw material plugging agent in the formulas of Comparative Examples 3, 6 and 9, Comparative Examples 1, 2, 4, 5, 7 and 8 were used as comparisons.
[0113] The plugging performance and compressive strength test results are shown in Table 3. It can be seen from Table 3 that at 150°C, the addition of the raw plugging agent can significantly improve the plugging ability of the high-density plugging cement slurry of the present invention for 0.25 mm cracks.
[0114] Embodiment 26:
[0115] According to the density of each embodiment in Table 2, at 2.1 g / cm3 , 2.2g / cm 3 , 2.3g / cm 3 , 2.4g / cm 3 , 2.5g / cm 3 and 2.6 g / cm 3 One example is selected from each of the density examples, that is, the high-density plugging cement slurries obtained in Examples 14, 16, 18, 20, 21 and 23 of the present invention are tested for plugging performance of 1.5 mm cracks at 150°C.
[0116] The test results are shown in Table 4. It can be seen from Table 4 that at 150°C, the high-density plugging cement slurries obtained in Examples 14, 16, 18, 20, 21 and 23 of the present invention have good plugging performance for 1.5 mm cracks.
[0117] Embodiment 27:
[0118] In order to test the applicable temperature range of the high-density plugging cement slurry of the present invention, the high-density plugging cement slurries obtained in Examples 14, 16, 18, 20, 21 and 23 of the present invention were subjected to performance tests at 120°C. The tests included density (g / cm 3 ), thickening time (min, 130℃ / 70MPa), API water loss (mL), compressive strength (MPa, 24h / 150℃), free liquid (%), fluidity (cm) and sedimentation stability (g / cm 3 ).
[0119] The test results are shown in Table 5, where the water loss is measured at 102°C for 0.5h and 90°C. The compressive strength data is measured after curing at 102°C for 0.5h and 120°C for 24h. It can be seen from Table 5 that at 120°C, the thickening time, API water loss and other properties of plugging cement slurries of various densities have reasonable changes; the compressive strength of cement paste has slightly decreased, but is still greater than 20MPa. This is because the molecular thermal motion speed decreases after the temperature is reduced, but the high-density plugging cement slurry of the present invention can still maintain good performance under the construction condition of 120°C, meeting the construction design requirements.
[0120] Embodiment 28:
[0121] The high-density plugging cement slurries obtained in Examples 14, 16, 18, 20, 21 and 23 of the present invention were tested for plugging performance on cracks of 0.25 mm and 1.5 mm at 120°C.
[0122] The test results are shown in Table 6. It can be seen from Table 6 that under 120°C, for cracks with a width of 0.25 mm, the high-density plugging cement slurries of various densities of the present invention all have good plugging performance, which is manifested as a leakage of no more than 25 mL over a pressure-bearing time of 10 minutes. For cracks with a width of 1.5 mm, the leakage of the high-density plugging cement slurry of the present invention can still be controlled within 50 mL. By comparing the test data under 150°C, it can be found that the compressive strength is slightly reduced and the elastic modulus is slightly increased.
[0123] Through Examples 24 to 28, it can be concluded that the high-density plugging cement slurry of the present invention is suitable for use at 120°C to 150°C. For 2.1 g / cm 3 Up to 2.6g / cm 3 The density system has good high temperature resistance, can effectively improve the plugging ability of fractured formations and improve cementing quality.
[0124] In summary, the high-density plugging cement slurry of the present invention has good rheological properties, good adaptability to fracture channels, good water loss reduction, leakage prevention and pressure bearing effects, and is suitable for cementing construction of high-temperature wells with a circulation temperature of 120°C to 150°C, and can effectively address the serious risk of leakage of high-density cementing slurry in fractured formations.
[0125] The above technical features constitute the embodiments of the present invention, which have strong adaptability and implementation effect. Non-essential technical features can be added or reduced according to actual needs to meet the requirements of different situations.
[0126] Table 1
[0127]
[0128]
[0129] Table 2
[0130]
[0131]
[0132] Table 3
[0133]
[0134]
[0135] Table 4
[0136]
[0137] Table 5
[0138]
[0139] Table 6
[0140]
[0141]
Claims
1. A high-density plugging cement slurry, characterized in that The raw materials include, by weight, 100 parts of G-grade oil well cement, 46 to 74 parts of water, 2.0 to 3.5 parts of plugging agent, 2.0 to 4.0 parts of calcium carbonate, 4.0 to 6.0 parts of fluid loss reducer, 1.0 to 4.5 parts of dispersant, 1.5 to 2.5 parts of retarder, 4.0 to 10.0 parts of microsilica powder, 30.0 to 45.0 parts of quartz sand and 10.0 to 150.0 parts of weighting agent.
2. The high-density plugging cement slurry according to claim 1, characterized in that The plugging agent is obtained by the following method: In the first step, 50 to 60 parts of deionized water are added into a reactor, nitrogen is introduced, and 15 to 20 parts of acrylic acid are added into the reactor under stirring; In the second step, NaOH is added to the reactor to adjust the pH value of the solution in the reactor to 7 to 9; The third step is to add 2.5 to 3.0 parts of acrylamide, 15 to 18 parts of 2-acrylamido-2-methylpropanesulfonic acid and 2 to 3 parts of glass fiber to the reactor in sequence, stir evenly, then drop 0.2 to 0.5 parts of ammonium persulfate, 0.2 to 0.5 parts of sodium sulfite and 0.1 to 0.3 parts of N,N-methylenebisacrylamide in sequence, control the reaction temperature of the reactor to 50°C to 60°C, rinse the reaction product 2 to 3 times until the reaction is completed, and dry it to obtain a plugging agent.
3. The high-density plugging cement slurry according to claim 1 or 2, characterized in that The fluid loss additive is obtained by the following method: The first step is to add 30 to 40 parts of deionized water into a reactor, introduce nitrogen, and under stirring conditions, sequentially add 8 to 10 parts of 2-acrylamido-2-methylpropanesulfonic acid, 0.1 to 0.2 parts of N-vinyl imidazole, 0.1 to 0.2 parts of N-vinyl pyrrolidone, 1 to 2 parts of acrylamide and 0.2 to 0.3 parts of maleic anhydride into the reactor, and stir evenly; In the second step, NaOH is added to the reactor to adjust the pH value of the solution in the reactor to 7 to 9; The third step is to drop 0.1 to 0.2 parts of ammonium persulfate into the reactor, and control the reaction temperature of the reactor to 50° C. to 60° C. until the reaction is completed to obtain a fluid loss reducer.
4. The high-density plugging cement slurry according to any one of claims 1 to 3, characterized in that The density of quartz sand is 2.65g / cm 3 Up to 2.80g / cm 3 , average particle size 50μm to 120μm.
5. The high-density plugging cement slurry according to any one of claims 1 to 4, characterized in that The density of microsilica powder is 2.00g / cm 3 Up to 2.35g / cm 3 , average particle size 1μm to 25μm.
6. The high-density plugging cement slurry according to any one of claims 1 to 5, characterized in that The weighting agent is one or more of micro manganese and iron ore powder.
7. The high-density plugging cement slurry according to any one of claims 1 to 6, characterized in that The retarder is retarder RCR-211S.
8. The high-density plugging cement slurry according to any one of claims 1 to 7, characterized in that The dispersant is dispersant RCY-100.
9. The high-density plugging cement slurry according to any one of claims 1 to 8, characterized in that It is obtained by the following method: first, the required amounts of plugging agent, calcium carbonate, fluid loss additive, dispersant, retarder, microsilica powder, quartz sand and weighting agent are mixed to obtain a mixture; then, the mixture and the required amount of water are added to the required amount of G-grade oil well cement and stirred evenly to obtain a high-density plugging cement slurry.
10. A method for preparing a high-density plugging cement slurry according to any one of claims 1 to 8, characterized in that The method is as follows: first, the required amounts of plugging agent, calcium carbonate, fluid loss additive, dispersant, retarder, microsilica powder, quartz sand and weighting agent are mixed to obtain a mixture; then, the mixture and the required amount of water are added to the required amount of G-grade oil well cement and stirred evenly to obtain a high-density plugging cement slurry.